2021
DOI: 10.3389/fsurg.2021.638057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surgical Complications With Respect to the Surgical Indication: Proposal for a Novel Index

Abstract: Introduction: The Clavien–Dindo classification is a broadly accepted surgical complications classification system, grading complications by the extent of therapy necessary to resolve them. A drawback of the method is that it does not consider why the patient was operated on primarily.Methods: We designed a novel index based on Clavien–Dindo but with respect to the surgical indication. We surveyed an international panel of otolaryngologists who filled out a questionnaire with 32 real case-inspired scenarios. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Elective surgery was performed for a range of ENT conditions. We used a standardized quality assessment for reporting post-operative complication and found no life-threatening, disabling complications and no postoperative sequelae ( Dindo et al, 2004 ; Gonçalves et al, 2020 ; Morand et al, 2021 ; Kotisalmi et al, 2022 ). A recent report concluded that the risk of surgical complications and postoperative mortality in PLWH with controlled HIV and higher CD4 counts was similar to HIV-uninfected individuals ( Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elective surgery was performed for a range of ENT conditions. We used a standardized quality assessment for reporting post-operative complication and found no life-threatening, disabling complications and no postoperative sequelae ( Dindo et al, 2004 ; Gonçalves et al, 2020 ; Morand et al, 2021 ; Kotisalmi et al, 2022 ). A recent report concluded that the risk of surgical complications and postoperative mortality in PLWH with controlled HIV and higher CD4 counts was similar to HIV-uninfected individuals ( Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elective surgery was performed for a range of ENT conditions. We used a standardized quality assessment for reporting post-operative complication and found no life-threatening, disabling complications and no postoperative sequelae (Dindo et al, 2004;Gonçalves et al, 2020;Morand et al, 2021;Kotisalmi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To classify the severity of complications after gastrointestinal surgical procedures, the Clavien–Dindo classification system is commonly used [ 14 ]. This classification consists of five grades in which grades three and four are further subdivided into A and B subgrades, and grade five indicates mortality [ 3 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To classify the severity of complications after gastrointestinal surgical procedures, the Clavien–Dindo classification system is commonly used [ 14 ]. This classification consists of five grades in which grades three and four are further subdivided into A and B subgrades, and grade five indicates mortality [ 3 , 14 ]. Each grade depends on the required intervention to resolve the complications, the higher the grade is, the more complex the intervention needed [ 3 , 14 ].…”
Section: Introductionmentioning
confidence: 99%